Flexibility, dynamic balance and core stability for injury prevention in university athletes - Villaquiran-Hurtado, Andrés; Molano-Tobar, Nancy Janneth; Portilla-Dorado, Enmanuel; Tello, Andrés (Universidad y Salud, 2020)
Introduction: Competitive sports demand intensive physical conditioning that leads to an increased risk of injury, consequently affecting the health, physical performance, participation in training, competition, and sport achievements of athletes. Objective: To determine core stability, lower limb dynamic balance and flexibility characteristics in university athletes. Materials and methods: A cross-sectional study with 86 university athletes, which corresponds to 25% of the university population. Core stability, lower limb dynamic balance, and flexibility of the posterior chain, shoulders and hip region were evaluated. The assessment guide from the public policy guidelines in sports sciences for the prevention of injuries was taken into account. Results: 83.7% of athletes displayed a normal body mass index and 47.5% showed an average flexibility in the Sit and Reach test without the presence of hip retractions. Regarding the core, 77.9% of the participants showed a poor stability and 47% had a risk of injury due to the differences between the lower extremities in the dynamic balance. Conclusions: These results suggest implementing injury prevention programs for university athletes.